Improving The Life Quality Of Low-Income Communities Through Hydroponic Bean Sprouts Business (Journal of Saintech Transfer, 2020)
This Community service was carried out on the groups of  people from various backgrounds who did not have permanent jobs. The purpose of community service is to help people who have low incomes that do not adequately meet their daily needs by creating business opportunities. The target to be achieved is to improve the standard of their living within the limited space and funds they have, to become an adequate entrepreneur and have a decent standard of living. The method used was to give lectures and practice in making hydroponic bean sprouts. After training, the trainees have mastered how to make hydroponic bean sprouts, done their own business, and have began to enjoy the results of their bean sprouts sales